Ultrasonic Study of Amino Acids in Aqueous Urea Mixture at 298K - PALANI, R.; SENTHILNATHAN, R. (Asian Journal of Chemistry, 2010)
Ultrasonic velocity (U), density (ρ) and viscocity (η) have been measured for three amino acids viz., glycine, L-alanine and L-serine in the aqueous urea (0.1 m) at 298K. Using the experimental values, the adiabatic compressibility (β), change in adiabatic compressibility (Δβ), relative change in adiabatic compressibility (Δβ/βº), apparent molal compressibility (ϕK) apparent molal volume (ϕV), limiting apparent molal compressibility ( ϕoK ), limiting apparent molal volume ( ϕoV and their constant (SK, SV) and viscosity B-coefficient were calculated for all the ternary systems. The results are interpreted in the light of intermolecular interaction in terms of the structure-making or structure-breaking effect of these amino acids in the mixture.